Assessment of China's Poor County Program. Issue 3 (2nd July 2016) - Fan, Jin; Guo, Xiumei; Marinova, Dora; Zhao, Dingtao; Zhang, Minxian
ABSTRACT: China made remarkable progress in rural poverty alleviation. A major policy instrument is the County Level Poverty Alleviation Program, which has vast policy support but is also criticized for targeting errors, misuse of funds, and making poverty both shameful and attractive. Whether this program, or the country's economic growth in general, is the main force in poverty reduction is the question addressed in this article, analyzing data for the 592 poor counties. The response to the economic growth–policy alleviation conundrum is that a push for social wellbeing and empowerment is needed together with economic growth to achieve major poverty improvements.